Gambaran Biaya dan Lama Rawat Inap Pada Pasien Diare Akut Anak Yang Menggunakan Kombinasi Suplemen Zink-Probiotik - Nurmainah Nurmainah; Ressi Susanti; Esy Nansy (Fakultas Farmasi Universitas Setia Budi, 2016)
Diarrhea is an endemic disease that has the potential for extraordinary events, which can lead to death. Treatment of diarrhea quickly and appropriately needs to be done, especially in pediatric patients. Giving supplements zinc and probiotics singly known to accelerate healing diarrhea in pediatric. The purpose of this study is to describe the cost and lenght of stay in patients with acute diarrhea of children who use a combination of zinc-probiotics supplements during their admission in the hospital. This is an observational research method with cross sectional study design that is descriptive. The data collection is done retrospectively database of pediatric patients hospitalized for acute diarrhea in RSUD Sultan Syarif Mohamad Alkadri Pontianak during September 2014-June 2015. The results of this study were all patient with acute diarrhea in hospitalized using combination of supplements zinc-probiotic (100%). The average length of stay in patients with acute diarrhea with mild dehydration for 2.42 days, while the average length of hospitalization in patients with acute diarrhea with mild dehydration is accompanied by infection during 4.26 days. Meanwhile, the average cost of hospitalization in patients with acute diarrhea with mild dehydration Rp. 560,248.48±198,127.01 whereas patients with mild dehydration from acute diarrhea accompanied infections spend an average cost of hospitalization by Rp.930.542,10 ± 346,312.35. The conclusion of this research was the combination of zinc and probiotics supplements for the treatment of acute diarrhea provides a brief hospitalization. It adversely affects the average cost of hospitalization in pediatric patient with acute diarrhea.